PERBEDAAN HASIL BELAJAR SISWA TENTANG RELASI DAN FUNGSI DALAM PEMBELAJARAN MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DAN PEMBELAJARAN LANGSUNG - Salajang, Santje; Mangobi, James Uriel; Lasut, Meicy Maria (Universitas Negeri Manado, 2020)
ABSTRACT. This study was conducted to determine the difference in student learning outcomes in learning relation and functions, between a group of students who learn using Think Pair Share (TPS) type of cooperative learning model and another group with direct instruction. This research apply the Posttest-Only Control Group Design. The subjects in this study were class VIII A as an experimental class consisting of 26 students and class VIII B as a control class consisting of 26 students in SMP Negeri 3 Tondano in the academic year 2019/2020. The instrument used was a test of relations and function material in essay form. Data collection techniques are through the posttest in the experimental class and the control class. Based on hypothesis testing using t-test statistics obtained t_count = 4,0007 and t_tabel = 2.310914 at the real level of 0.05 thus H_0 was rejected. The results of the study concluded that there were differences in the average learning outcomes of students who were taught using the Cooperative Think Think Share type model and direct learning. Keywords: Mathematics Learning Outcomes, Relation and Function, Think Pair Share